Dyslexia Pocketbook - Bennett, Julie (Alresford : Teachers' Pocketbooks, 2006)
This pocketbook is a practical guide to helping dyslexic students overcome their learning barriers and unlock their potential. It gives an outline of what dyslexia is, information on possible learning profiles and suggested solutions and techniques.
Includes bibliographical references (p. 122-123).
Keywords: Dyslexia; Dyslexic children -- Education; Education